Conception of public school teachers in São José do Egito, Pernambuco, about Environmental Education - Tavares, Robson Victor; Cavalcante, Anna Beatriz Amorim; Oliveira, Habyhabanne Maia; Silva, Edevaldo; Almeida, Elzenir Pereira Oliveira (Scientia Plena, 2016)
The inclusion of environmental issues in formal education is recent. In this reality, the present study aimed to analyze the conception that teachers from public schools in São José do Egito, Pernambuco - Brazil, have on relevant issues and actions for Environmental Education. We interviewed 22 teachers through a structured questionnaire consisting of 10 questions focusing on environmental matters. We found that 95.5% of the interviewees showed interest in studying environmental issues and considered themselves as responsible for any environmental damage occurring. They all stated that environmental damage worries them and 72.7% have already tried to change this situation. They (72.7%) believe that there can be economic and social development without causing environmental impacts. Half of them consider the citizens as the main responsible for the damage to the environment and at the same time as the most involved with its protection. In addition, 40.9% said that the school where they work treats environmental issues superficially and 59.1% said the textbook as insufficient material to address environmental issues. The low school performance and the lack of teacher training in Environmental Education compromise the critical education of students regarding environment preservation.